2012
DOI: 10.1542/peds.2011-3056
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Voluntary Parental Decision-Making in Pediatric Oncology

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Valid parental permission requires that the decision be both informed and voluntary. Previous research has focused on the informational components of decision-making (eg, disclosure and understanding), with little empirical attention to the voluntariness of decisions. WHAT THIS STUDY ADDS:We address this gap by examining the voluntariness of parents making research or treatment decisions in pediatric oncology. We identify demographic and contextual correlates of voluntariness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 31 publications
0
31
1
Order By: Relevance
“…Appropriate information requires to establish a true dialogue and communication process (not a mere transmission), 1,33,34 allowing to tailor information and secure its meaning. 7,20,35,36 Family needs shall guide this dialogue; 30,37,38 only one parental preference cannot be accommodated: the wish not to be informed.…”
Section: Consentmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate information requires to establish a true dialogue and communication process (not a mere transmission), 1,33,34 allowing to tailor information and secure its meaning. 7,20,35,36 Family needs shall guide this dialogue; 30,37,38 only one parental preference cannot be accommodated: the wish not to be informed.…”
Section: Consentmentioning
confidence: 99%
“…They mostly focus on interventions which might improve quality of parental consent (stepwise approach, nurses, leaflets, videos, individual or family conference). 32,36,38,39,[42][43][44] Only two alternatives to standard consent settings are addressed: 1° 'staged' consent (to obtain consent to randomisation at distance from inclusion) 20 and 2° 'differed' consent in emergency-like situations (waiver of consent at inclusion). 19 Closer attention is paid to the following issues: voluntariness of participation, impact that seeking consent can have on patients and parents, and family dynamics.…”
Section: Consentmentioning
confidence: 99%
“…Retinoblastoma education using graphics-Chiu et al levels were associated with lower perceived voluntariness. 19 It also has implications on clinicians. In a study analyzing informed decision-making among adults with lower education level, the group randomized to using a decision aid attained adequate knowledge to make an informed choice for bowel cancer screening compared with the control group using the standard government information.…”
Section: Group E Eyesmentioning
confidence: 99%
“…Previous studies investigating parental and young adult preferences for informed consent in clinical trials in pediatric oncology settings have demonstrated that participants generally prefer: (1) to receive more information but risk feeling overwhelmed with the quantity or pace of information provided; (2) that the information be presented in a stepwise and organized manner; and (3) to be given sufficient time to process the information, especially in the context of their emotional state, before making a decision [1,2]. The presentation of additional audio or visual learning materials is also suggested [1].…”
Section: Introductionmentioning
confidence: 99%